AN ANALYSIS OF THE MOST DOMINANT POLITENESS MAXIM IN THE MAIN CHARACTER’S DIALOGUES IN THE HELP FILM - Nadiah Athifah; Nurlaila Nurlaila (Universitas Gunadarma, 2022)
According to Leech (in Cruse, 2000) politeness maxim is needed to maintain of harmonious and smooth social relations in the face of the necessity to convey convoluted messages. The aim of this research is to find out the most dominant types of politeness maxim used by the main character in The Help film. The researchers use a descriptive qualitative method. The data of this research are the utterances and the dialogues between Aibileen as a main character with other characters. The data source is The Help film. The result of this research shows that there are 43 data of politeness maxims in The Help film. The maxims include agreement maxim (12), praise maxim (9), consideration maxim (8), generosity maxim (6), modesty maxim (3), tact maxim (3), and sympathy maxim (2). Thus, the most dominant maxim that is used by the main character of The Help film is agreement maxim (12), which is minimize disagreement with the hearer and maximize agreement with the hearer. It is concluded that the main character reduce disagreement frequently.